A qualitative study of leadership characteristics among women who catalyze positive community change. - Folta, Sara C.; Seguin, Rebecca A.; Ackerman, Jennifer.; Nelson, Miriam E. (2016)
Background: Leadership is critical to making changes at multiple levels of the social ecological model, including the environmental and policy levels, and will therefore likely contribute to solutions to the obesity epidemic and other public health issues. The literature describing the relative leadership styles and strengths of women versus men is mixed and virtually all research comes from sectors outside of public health. The purpose of this qualitative study is to identify specific leadership skills and characteristics in women who have successfully created change predominantly within the food and physical activity environments in their communities and beyond. The second purpose of this study is to understand best practices for training and nurturing women leaders, to maximize their effectiveness in creating social change.; Keywords: Women, Leadership, Public health, Social ecological model, Obesity prevention.; Springer Open.